Integrating Mental Health Services Into Perinatal Care: Challenges and Opportunities - Feyissa GT; Pouget ER; Kitila SB; Terfa YB; Wong T (Journal of Multidisciplinary Healthcare)
Garumma T Feyissa,1 Enrique R Pouget,1 Sena B Kitila,2 Yonas Biratu Terfa,2 Tracy Wong1 1Department of Health and Nutrition Sciences, Brooklyn College, City University of New York, Brooklyn, NY, 11210, USA; 2School of Nursing, Institute of Health, Jimma University, Jimma, EthiopiaCorrespondence: Garumma T Feyissa, Department of Health and Nutrition Sciences, Brooklyn College, City University of New York, Brooklyn, New York, 11210, USA, Email garumma.feyissa@brooklyn.cuny.eduIntroduction: In most low-income countries, including Ethiopia, mental healthcare has not been fully integrated into perinatal services. As a prerequisite for the integration, this project aimed to understand the facilitators and barriers to integrating mental health services into perinatal care.Methods: This exploratory qualitative research used in-depth interviews with 25 purposely selected participants representing diverse stakeholders (perinatal women, health service coordinators and providers, and community health workers and community volunteers). The transcribed interviews were coded and analyzed using Atlas ti Software.Results: The study found the following major impediments to providing and receiving perinatal mental health services: a) the lack of sense of ownership and accountability, b) constraints related to institutional resources and infrastructure; c) inequitable access to healthcare; d) the absence of supportive policy framework with focus on perinatal mental health; e) cultural beliefs and community perceptions; f) limited support from stakeholders; g) limited practice of compassionate and respectful care; and h) poor service planning and coordination. The opportunities for the integration of mental healthcare into perinatal services are a) the presence of maternal and child health (MCH) and mental health professionals, b) a conducive structure linking hospitals to the community and c) a convenient institutional infrastructure, d) higher level government support. Strategies suggested for the integration are awareness creation, capacity building, development of guidelines and checklists, and stakeholder engagement.Conclusion: The current Ethiopian primary healthcare system offers a conductive structure for the integration of mental healthcare into perinatal services. The existing bottlenecks against the service integration can be tackled by training health professionals, community sensitization, and advocacy and generating evidence that leads to the development of evidence-based implementation tools and health service delivery models tailored to local needs. The strategies outlined in this study may be used to design perinatal mental health services at multiple levels.Plain Language Summary: Why was this studyconducted?This study explored barriers and facilitators to integrate mental health into maternal and child health services.What did this study find?The absence of providers trained on perinatal mental health, absence of implementation tools, and limited focus on perinatal mental health deter the integration of mental health into MCH services.Cultural perceptions also deter seeking service for mental health problems during perinatal period.The existing primary healthcare structure of Ethiopia offers a favorable condition to integrate mental health into maternal and child health services.What do these results mean?The integration of mental health into MCH services requires community sensitization, engagement of stakeholders and training of providers at different levels. The service integration also requires the development of implementation guidelines and tools.The strategies outlined in this study might be used to design perinatal mental health services at multiple levels with the Ethiopian Healthcare System.Keywords: mental health, perinatal mental health, Ethiopia, service integration, maternal and child health